2021
DOI: 10.3390/geriatrics6030082
|View full text |Cite
|
Sign up to set email alerts
|

Interventions against Social Isolation of Older Adults: A Systematic Review of Existing Literature and Interventions

Abstract: Social isolation is widespread among older adults, especially those confined to living in nursing homes and long-term care facilities. We completed a systematic review evaluating the effectiveness of 20 interventions used to combat social isolation in older adults. A scoring mechanism based on the Joanna Briggs Appraisal Checklist was utilized to determine the quality of the studies. Searches were conducted in “MedLine”, “PubMed”, “PsycINFO” and “Aging and Mental Health”. Studies completed on group and person-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Only 12 of the included reviews assessed primary studies for quality or risk of bias (Chen et al, 2022 ; Filges et al, 2020 ; Gualano et al, 2018 ; Hui et al, 2020 ; Hyde et al, 2014 ; Jenkinson et al, 2013 ; Lovell et al, 2015 ; Manjunath & Manoj, 2021 ; Marco-Gardoqui et al, 2020 ; Milbourn et al, 2018 ; Owen et al, 2022 ; Willems et al, 2020 ). The tools most commonly used to assess study quality were the Effective Public Health Practice Project tool (Lovell et al, 2015 ; Owen et al, 2022 ) and JBI checklists (Manjunath & Manoj, 2021 ; Marco-Gardoqui et al, 2020 ). Those that assessed risk of bias mainly utilised Cochrane tools ROB-2 for randomised controlled trials (RCTs) (Gualano et al, 2018 ; Jenkinson et al, 2013 ), and ROBINS-I for non-RCTs (Chen et al, 2022 ; Filges et al, 2020 ; Gualano et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 12 of the included reviews assessed primary studies for quality or risk of bias (Chen et al, 2022 ; Filges et al, 2020 ; Gualano et al, 2018 ; Hui et al, 2020 ; Hyde et al, 2014 ; Jenkinson et al, 2013 ; Lovell et al, 2015 ; Manjunath & Manoj, 2021 ; Marco-Gardoqui et al, 2020 ; Milbourn et al, 2018 ; Owen et al, 2022 ; Willems et al, 2020 ). The tools most commonly used to assess study quality were the Effective Public Health Practice Project tool (Lovell et al, 2015 ; Owen et al, 2022 ) and JBI checklists (Manjunath & Manoj, 2021 ; Marco-Gardoqui et al, 2020 ). Those that assessed risk of bias mainly utilised Cochrane tools ROB-2 for randomised controlled trials (RCTs) (Gualano et al, 2018 ; Jenkinson et al, 2013 ), and ROBINS-I for non-RCTs (Chen et al, 2022 ; Filges et al, 2020 ; Gualano et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Publication of reviews spanned from 1998 (Wheeler et al, 1998 ) to 2022 (Chen et al, 2022 ; Howard & Serviss, 2022 ; Owen et al, 2022 ), with search dates up to 2020 (Chen et al, 2022 ; Howard & Serviss, 2022 ; Owen et al, 2022 ). Most reviews focused on older people (Anderson et al, 2014 ; Bonsdorff & Rantanen 2011 ; Cattan et al, 2011 ; Chen et al, 2022 ; Filges et al, 2020 ; Gualano et al, 2018 ; Manjunath & Manoj, 2021 ; Milbourn et al, 2018 ; Okun et al, 2013 ; Onyx & Warburton, 2003 ; Owen et al, 2022 ; Wheeler et al, 1998 ), with inclusion criteria ranging from aged over 50 years (Anderson et al, 2014 ; Cattan et al, 2011 ; Manjunath & Manoj, 2021 ; Milbourn et al, 2018 ) to a sample with a mean age of 80 years or above (Owen et al, 2022 ). Only one review focused specifically on adolescents (Goethem et al, ( 2014 )).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 17 systematic reviews of effectiveness of interventions which aim to mitigate social isolation and/ or loneliness in older adults [12,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The characteristics of these reviews are presented in Table 2.…”
Section: Description Of Included Systematic Reviewsmentioning
confidence: 99%
“…Social isolation may also contribute to our findings. A recent systematic review on social isolation 61 showed that group interventions may improve mental and physical health, alleviate social isolation, and result in increased social activation among older adults. Such interventions may also help patients with kidney failure to find potential donors by fostering meaningful relationships.…”
Section: Discussionmentioning
confidence: 99%